Pengaruh Penggunaan Aplikasi Canva terhadap Motivasi Belajar Peserta Didik - Meilisa Sajdah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research basically aims to find, describe and analyze the influence between the variable use of the Canva X1 application and the variable student learning motivation (Y). where the main problem is the lack of student motivation to learn in the era of the onslaught of gedzet. As an effort to find out the influence of usage on the learning motivation of class VII students at Ibnu Rushd Islamic Middle School. This research uses quantitative research methods with a large sample of 60 respondents. Data was collected using a closed questionnaire instrument in the form of multiple choices in which variable X1 consisted of 4 questions, and variable Y had 2 questions using a Likert scale. So, the questionnaire variable for using the Canva application has 4 questions, and the student learning motivation questionnaire has 2 questions so that the total of the questionnaires is 6 questions. In this research, it is explained that there is a significant influence between the use of the Canva application on students' learning motivation after carrying out associative analysis, in accordance with the research results of Thomas, O Bannon and Bolton, they found that 'use of the Canva application' can influence students' learning motivation. The research data collected was analyzed using descriptive analysis techniques with the average variable value for using the Canva application in the medium category being 27 students or 45%, and student learning motivation being 35 students or 58.3%. Then proceed with the Chi Square normality test on the use of Canva chi square, namely 248, 0673913 and to find the level of influence entered into the contingent coefficient formula, it was obtained 0.897 or